Mind–body group treatment for women coping with infertility: a pilot study. (June 2015) - Psaros, Christina; Kagan, Leslee; Shifren, Jan L.; Willett, Jessica; Jacquart, Jolene; Alert, Marissa D.; Macklin, Eric A.; Styer, Aaron K.; Denninger, John W.; LaRoche, Katie L.; Park, Elyse R.
Abstract: Objectives : To evaluate the feasibility of a 10-week mind–body intervention (MBI) for women coping with fertility challenges, examine the impact of an MBI on psychological distress and cortisol levels, and assess adherence to MBI skills 12-months after completion of the intervention. Design : Prospective open pilot study of 51 women with infertility enrolled in a group MBI. Psychological variables and salivary cortisol levels were obtained pre- and post-intervention; a 12-month follow-up survey assessed MBI skill adherence. Participants completed practice logs throughout the intervention. Results : Participants attended an average of eight sessions (SD = 2.0), and practiced mind–body techniques which elicited the relaxation response (RR) an average of 5.9 (SD = 0.8) days/week and 20.1 (SD = 9.9) min/day; 80% completed the post-treatment assessment. The intervention resulted in a significant increase in perceived social support and a decrease in depressive symptoms and perceived stress; however, there were no significant changes in cortisol levels. Sixty-eight percent of the participants completed the 12-month follow-up, with 51% reporting continuation of RR-eliciting practice. Conclusion : This group of women with infertility provided with an MBI showed decreased symptoms of depression and stress and increased perceived social support. The protocol was feasible and participants reported a high degree of adherence and maintenance to the skills taught during the intervention. The findings indicate the value of appropriate evaluation against a control group.